Pra-Rancangan Pabrik Biobutanol dari Molase Melalui Fermentasi Ekstraktif dengan Kapasitas 25.000 Ton/Tahun - Ariel Seanhan Haezer (Fakultas Teknik, 2024)
A biobutanol plant was established to supply the entire domestic demand for butanol since there are currently no biobutanol plants operating in Indonesia. The biobutanol plant, which is designed to produce 25,000 tons per year, will commence operations in 2026 in Ngoro District, Mojokerto Regency, East Java, on a land area of 4.5 hectares. The process requires 58,008.85 tons of molasses annually. Biobutanol is produced through extractive fermentation in a batch reactor at 30°C and 1 atm pressure. The reaction is exothermic, and the reaction temperature is maintained at 30°C using a cooling jacket coil. Butanol is separated from the bacteria and growth media using a filter press, then purified from impurities through distillation to a purity of 99.5%. The process also produces a by-product of 99.5% acetone, which is stored in storage tanks. Supporting utilities for the process include a water requirement of 115,666.6 kg/hour, steam requirement of 3,530,348.17 kg/hour, fuel requirement of 115.24 liters/hour, and electricity requirement of 98.23 kWh/hour. The company is structured as a Limited Liability Company (PT) with a line and staff organizational structure. The plant employs 194 personnel categorized into shift and non-shift workers. Based on economic analysis, the biobutanol plant is deemed feasible considering various aspects including an Annual Cash Flow (ACF) of Rp889,461,515,027, a Pay Out Time (POT) of 3.1 years, and a Break Even Point (BEP) of 44.8%.
Entry oleh Arif 2026 Maret 16
Keywords: Plant; Biobutanol; Process